Rayleigh wave propagation in semi-infinite flexoelectric dielectrics. (15th April 2019) - Qi, Lu
Abstract: With consideration of the static bulk flexoelectric effect, dynamic bulk flexoelectric effect, strain gradient elastic effect and micro-inertia effect, Rayleigh wave propagation in semi-infinite centrosymmetric flexoelectric dielectrics is investigated and the dispersion relation is derived. Numerical results of the Rayleigh wave propagation in single crystal SrTiO3 indicate that, the strain gradient elastic effect and the micro-inertia effect have competing influences on the wave velocity, and the ratio of the corresponding two internal length scales is essential to the dispersion curve. However, these effects are remarkable only when the wave number is relatively large. In addition, the static bulk flexoelectric effect is found to reduce the Rayleigh wave velocity especially when the static bulk flexocoupling coefficient is large. Furthermore, influences of the dynamic bulk flexoelectric effect and the polarization gradient effect on the Rayleigh wave propagation are also examined that they both hinge on the flexocoupling coefficient other than the related material constants.